Voltametria adsortiva na determinação de traços e ultra-traços de Zr(IV), V(V),Ti(IV), Mo(VI), Hf(IV), Nb(V) e Ta(V) em águas naturais - Schneider, Alexandre Batista (2014)
Single sensitive sequential AdSV methods were developed and optimized for the determination of trace zirconium, vanadium, titanium and molybdenum in river, estuary and seawater, independent of the salinity and content of organic matter in the sample. The methods are based on the accumulation of Zr(IV)-and V(V)-cupferron-oxalic acid-1,3-diphenylguanidine complexes and the accumulation of Ti(IV)-and Mo(VI)-mandelic acid at the hanging mercury drop electrode (HMDE). Differential pulse, adsorption potential of -0.6, -0.2, -0.1 and -0.1 V (vs. Ag/AgCl), adsorption time of 400, 20, 120 and 1 s and scan rates of 0.01, 0.06, 0.02 and 0.02 V s-1 for Zr(IV), V(V), Ti(IV) and Mo(VI), respectively, were used as instrumental parameters. The reduction peak for the complexes of Zr(IV), V(V), Ti(IV) and Mo(VI) appeared nearly -0.95, -0.65, -0.85 and -0.4 V, respectively. The variations of the peak current as well as the peak potential of each metal complexes were plotted against the apparent ionic strengths. The proposed voltammetric methods were applied in German and Brazilian rivers and estuaries as well as in seawater from the North Sea collected at the north of Germany and the Atlantic Ocean, collected during scientific cruise between Chile and Germany, as interesting and very simple alternatives to very laborious and time-consuming pre-existent methods, based on outline pre-concentration and separation from the matrix and subject to external contamination. The limits of detection and determination were in the range of ppt-levels and the methods accuracy were evaluated by recoveries tests and by measuring V(V) and Mo(VI) in two NRCC reference materials. Estuarine mixtures experiments were also carried out with the aim to get more insight on the distribution of Ti(IV), Zr(IV), Mo(VI) and V(V) along the estuaries of the rivers Rhine, Weser and Elbe with the North Sea. In this context, natural fresh waters were mixed with seawater at different ratios.